Black energy intensity versus green energy intensity: implications for sustainable development. (1st January 2014) - Yang, Peter
This study attempted to identify the common trends for the 'black' and 'green' economic development of the major developed and developing countries as well as exceptions to these trends. It investigated these economies' energy and carbon dependences in the last 42 years and their renewable energy growths in the last ten years. In addition to the traditional concept of 'energy intensity', this study developed the terms of 'black energy intensity' and 'green energy intensity' to test the hypothesis that the decrease in the former and the increase in the latter indicated an economy's degree of transition to the sustainable development. It examined the major economies' green energy intensities both with and without hydropower. The results revealed however that only a few EU countries passed both tests. Based on the major economies' black energy intensities, carbon intensities, and green energy intensities, the study discussed their policy implications for these economies' transformation to the sustainable development.